„Nauka o organizacji" a socjologia - Krężlewski, Jerzy (Wydział Prawa i Administracji UAM, 1984)
The article is an attempt at presentation how basic notions and ferms used by sociology of organization function in other sciences dealing with problems of organization as eg. praxiology, theory of organization and «management or psychology of organization. General reflections are concentrated around various ways of understanding of the notion of „organization" and around the so-called concept of system analysis of organization. The author advocates understand of organization as a set of rules of action or rules of functioning of groups or other human communities. He represents an opinion that organization cannot be identified in sociology with institution assi there are essential differences between them. The author attempts to present a relationship between organization and institution in sociolo¬ gical aspect on the grounds of (the proposed way of interpreting the notion of organization. The article includes critical remarks on the so-called system approach in sciences on organization. It is found that in most of the oases the system approach functions only as a language formation unable to contribuite any methodological qualities but a new slang. Treating the system approach as a new methodological directive assumes a p r i o r i , that any organization is a system which does not always correspond to social reality. For there are organizations not fulfilling their statute goals because they do not function as a system. The final part of reflections is an attempt at presentation of tasks of sociology in analysing organizations and explicating those mechanisms for the sake of practice which cause organizations to function as an integrated whole, as a social system.
„Sciences on organization" and sociology